1996
DOI: 10.1074/jbc.271.16.9801
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Membrane Transporter Associated with Intracellular Membranes by Phenotypic Complementation in the Yeast Saccharomyces cerevisiae

Abstract: A partial mouse cDNA was isolated by its ability to functionally complement a thymidine transport deficiency in plasma membranes of the yeast, Saccharomyces cerevisiae. The full-length cDNA encoded a previously unidentified 27-kDa protein (mouse transporter protein (MTP)) with four predicted transmembranespanning domains. MTP mRNA was detected in cells of several mammalian species, and its predicted protein sequence exhibited near identity (98%) with that of a human cDNA (HUMORF13). MTP and its homologs eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 42 publications
3
65
0
Order By: Relevance
“…Here, we report a novel interaction between MCOLN1 and the members of the LAPTM family. Although the cellular function of LAPTMs is not well understood, it has been suggested that LAPTMs might participate in the transport of small molecules across intracellular membranes (Hogue et al, 1996;Hogue et al, 1999). We found that MCOLN1 and LAPTMs colocalize to late endosomes and lysosomes and confirmed the interaction by coimmunoprecipitation in human cells.…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…Here, we report a novel interaction between MCOLN1 and the members of the LAPTM family. Although the cellular function of LAPTMs is not well understood, it has been suggested that LAPTMs might participate in the transport of small molecules across intracellular membranes (Hogue et al, 1996;Hogue et al, 1999). We found that MCOLN1 and LAPTMs colocalize to late endosomes and lysosomes and confirmed the interaction by coimmunoprecipitation in human cells.…”
Section: Introductionsupporting
confidence: 66%
“…Both clones were in-frame with the N-terminal half of ubiquitin. The function of LAPTMs is not completely understood but it has been suggested that they are transporters involved in the subcellular compartmentalization of different compounds (Hogue et al, 1996;Hogue et al, 1999). MCOLN1 protein binding to LAPTMs was confirmed by performing additional yeast twohybrid experiments.…”
Section: Identification Of Laptms As Novel Mcoln1 Binding Partnersmentioning
confidence: 84%
“…It is also 46% homologous at the amino-acid level to a human lysosome-associated transmembrane-4 protein, LAPTM4A. The ortholog of LAPTM4A in murine is a nucleoside transporter on intracellular membrane-bound compartments, and mediates a multidrug resistance phenotype in drug-sensitive strains of S. cerevisiae (Hogue et al, 1996;Cabrita et al, 1999). LAPTM4B shares a number of characteristics with other lysosome-associated proteins such as LAPTM5 (Adra et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the mLAPTM4A functions in the transport of nucleosides and/or nucleoside derivatives between the cytosol and the lumen of an intracellular membrane-bound compartment and may confer multidrug resistance upon expression in Saccharomyces cerevisiae (Hogue et al, 1996Cabrita et al, 1999).…”
mentioning
confidence: 99%